The Influence of Project-Based Learning Methods (PjBL) and Critical Thinking in Improving Student Learning Outcomes - Rafha Naisa Alifah; Marsofiyati (UNIVERSITAS SERAMBI MEKKAH, 2024)
The study aims to analyze the influence of the effect of project-based learning (PjBL) together with the skills of critical thinking toward student learning achievement. This type of research is a survey, using the sample of 35 respondents from UNJ students majoring in Economic and Administration. The technique uses the Proportional Stratified Random Sampling. Data were collected by using a questionnaire with a Likert scale model and tests and will be analyzed using descriptive and inferential statistics. The results of the analysis of the data show that PjBL significantly influences student learning achievement in the form of more active and applicative learning processes, and CT affects the learning outcome by allowing students to think analytically and critically in problem-solving. Combined application of PjBL and critical thinking skills gives better effect on the student achievement compared to the individual application of PjBL and critical thinking skills. This implies that the two can be used simultaneously for enhancing performance, an indicative benefit that they can be used together for improving learning.